USING THE MORPHOMETRIC CHARACTERISTICS OF WOOD RAW MATERIALS IN THE SAWMILL TECHNOLOGY (Innovation in Woodworking Industry and Engineering design, 2026)
The opportunities of use of uneven distribution of knots in wood raw material are considered at cutting lumber on sawn blanks.